Efficacy, safety and cardiovascular outcomes of once‐daily oral semaglutide in patients with type 2 diabetes: The PIONEER programme - Thethi, Tina K. (Diabetes Obes Metab, 2020)
Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are recommended for glycaemic management in patients with type 2 diabetes (T2D). Oral semaglutide, the first oral GLP‐1RA, has recently been approved for clinical use, based on the results of the randomized, Phase 3a Peptide InnOvatioN for Early diabEtes tReatment (PIONEER) clinical trials. The PIONEER programme tested oral semaglutide in patients with T2D of duration ranging from 3.5 to 15 years, from monotherapy through to insulin add‐on, in global populations and two trials dedicated to Japanese patients. Outcomes (glycated haemoglobin [HbA1c] and body weight reduction, plus other relevant efficacy and safety endpoints) were tested against both placebo and active standard‐of‐care medications. A separate trial evaluated the cardiovascular safety of oral semaglutide in patients with T2D at high cardiovascular risk. Over periods of treatment up to 78 weeks, oral semaglutide 7 and 14 mg once daily reduced HbA1c and body weight across the spectrum of T2D, and improved other diabetes‐related endpoints, such as fasting plasma glucose. Oral semaglutide provided significantly better efficacy than placebo and commonly used glucose‐lowering medications from the dipeptidyl peptidase‐4 inhibitor (sitagliptin) and sodium‐glucose co‐transporter‐2 inhibitor (empagliflozin) classes, as well as the subcutaneous GLP‐1RAs liraglutide and dulaglutide. Oral semaglutide was well tolerated in line with the known safety profile of GLP‐1RAs, with transient gastrointestinal events being the most common side effects reported. Cardiovascular safety was demonstrated for oral semaglutide in patients with cardiovascular disease or high cardiovascular risk. The results of the PIONEER programme suggest that oral semaglutide is efficacious and well tolerated for glycaemic control of T2D. The availability of oral semaglutide may help to broaden treatment choice and facilitate adoption of earlier GLP‐1RA treatment in the paradigm of T2D management.